PENGARUH FAKTOR-FAKTOR SOSIAL-EKONOMI TERHADAP PERILAKU PENGELOLAAN SAMPAH DOMESTIK DI NUSA TENGGARA TIMUR - Beni, Martinus Tulit; Arjana, IGB; Ramang, Ruslan (School of Postgraduate Studies, Diponegoro Univer, 2014)
In the attempt to implement sustainable development, there is a definition that the use of natural source to keep it uses by the next generation well, both in quantity and quality. It needs to be supported by caring the environment both by the government and the community itself. The community awareness can be seen at its role on the management of domestic garbage. Several socio-economic factors such as age, sex, education, income, job, and the knowledge of environment have effect on community awareness in the management of domestic garbage. This study used logistic regression model which aimed at measuring to what extend the effect of the socio-economic factors to domestic garbage management in East Nusa Tenggara Province in 2013. It uses secondary data of Environmental Awareness Behaviour Survey that done in 2013 by the Central Agency on Statistics. The result of this study used α = 0,05, showed that the variable of sex, age group of the head household among 40-59 years old and the knowledge of environment did not have effect on household garbage management behavioral. Level education of the patriarch and capital income affected positively on domestic garbage management behavioral. Variable of age group of the patriarch above 60 years old did negatively affected to the domestic garbage management behavioral. Although knowledge about the environment did not affect eco-friendly behavior, but the knowledge about the environment has to be continued to be disseminated to the public. Right knowledge about the behavior of environmental awareness is a major component of internal factors that can drive change one's attitude to be more concerned about the environment